Key Drivers of Customer Satisfaction on the E-Commerce Business - Muhammad Masyhuri (East Asian Journal of Multidisciplinary Research, 2022)
To survive in the e-retail business, current online retailers should compete with others to retain their customers. Tremendous efforts are required to meet the expectations of demanding online customers. This means that online businesses should understand what key factors determine customer satisfaction to survive in the current e-commerce business. The aim of this paper is to analyze the key factors of customer satisfaction for e-commerce companies. The methodology of this study is based on the work of (Yoon, 2007), which consists of customer service, fulfilment/reliability, ease of use, product/service offering, and security and privacy. The world's two leading e-commerce companies - Amazon and eBay - were selected as best practice examples for this case.